A Synergistic Capture Strategy for Enhanced Detection and Elimination of Bacteria1. Issue 23 (19th March 2014) - Li, Yong‐Qiang; Zhu, Bowen; Li, Yuangang; Leow, Wan Ru; Goh, Rubayn; Ma, Bing; Fong, Eileen; Tang, Mark; Chen, Xiaodong
Abstract Despite the advanced detection and sterilization techniques available today, the sensitive diagnosis and complete elimination of bacterial infections remain a significant challenge. A strategy is reported for efficient bacterial capture (ca. 90 %) based on the synergistic effect of the nanotopography and surface chemistry of the substrate on bacterial attachment and adhesion. The outstanding bacterial‐capture capability of the functionalized nanostructured substrate enables rapid and highly sensitive bacterial detection down to trace concentrations of pathogenic bacteria (10 colony‐forming units mL−1). In addition, this synergistic biocapture substrate can be used for efficient bacterial elimination and shows great potential for clinical antibacterial applications.